An Efficient Encrypted Digital Image Watermarking Scheme (International Journal of Scientific Research and Management (IJSRM), 2014)
Increasing in networked multimedia systems has an immediate need for copyright protection and security of multimedia data that is transferred through the network. Digital watermarking technology provides solutions for protecting multimedia data from illegal manipulations. In the proposed method, embedding of watermark is done by using Discrete Wavelet Transform (DWT) - Singular Value Decomposition (SVD), and then a private key is used for the encryption of watermarked image. At the other end the watermarked image is decrypted first using the private key then the watermark is extracted by applying the reverse process of embedding. Using DWT-SVD, modification in all frequencies allows the development of a watermarking scheme that is robust to a wide range of attacks, and without having the private key any one cannot delete or modify the watermark.